Heart of darkness : unraveling the mysteries of the invisible universe - Ostriker, J. P.; Mitton, Simon, 1946- (Science essentials (National Academy of Sciences (U.S.)), 2013)
"Heart of Darkness describes the incredible saga of humankind's quest to unravel the deepest secrets of the universe. Over the past thirty years, scientists have learned that two little-understood components--dark matter and dark energy--comprise most of the known cosmos, explain the growth of all cosmic structure, and hold the key to the universe's fate"--Jacket.